2008
DOI: 10.1007/s11104-008-9817-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of autotoxic compounds from fibrous roots of Panax quinquefolium L.

Abstract: Panax quinquefolium (American ginseng) is a perennial understory herb that has been widely used as a medicinal plant in China and other countries. Autotoxicity has been reported to be one of the major problems hindering the consecutive cultivation of American ginseng. However, the potential autotoxic compounds produced by the root of American ginseng are less well known. Here, we report the isolation and characterization of five groups of autotoxic compounds from aqueous extracts of the fibrous roots of Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
(3 reference statements)
1
58
0
Order By: Relevance
“…Autototoxicity is an important phenomenon in controlling population density in natural systems (He et al ., 2009). In tough lovegrass, it is a mechanism that possibly is involved in controlling the germination and growth of plants of the species itself, which could explain the gaps between their tussocks in the field .…”
Section: Shoot Growth (% Inhibition)mentioning
confidence: 99%
“…Autototoxicity is an important phenomenon in controlling population density in natural systems (He et al ., 2009). In tough lovegrass, it is a mechanism that possibly is involved in controlling the germination and growth of plants of the species itself, which could explain the gaps between their tussocks in the field .…”
Section: Shoot Growth (% Inhibition)mentioning
confidence: 99%
“…By applying natural blends of phytochemicals derived from root exudates of Arabidopsis to the soil, Badri et al (2013) found that phenolic-related compounds predominantly modulate the soil microbiome. Increasingly, studies have shown that particular autotoxins (phenolicrelated compounds) from root exudates not only directly suppress the growth of the plant itself (Asao et al 2007;He et al 2009;Kong et al 2008;Li et al 2012;Mahall and Pramanik et al 2001;Yu et al 2000), but also indirectly stimulate soil-borne pathogens, and thus enhance disease incidences (Manici et al 2004;Nicol et al 2003;Ye et al 2004;Zhang et al 2010). Autotoxins might influence the progression of soil-borne pathogens by modulating the resistance system of plants to pathogen infection (Nigh 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Soil sickness is usually found in agricultural crops, especially in medicinal plant (Zhang et al, 2005;He et al, 2009;Yin et al, 2009). Soil sickness may be attributed to autotoxicity, soil microflora imbalance and changes in soil physiochemical properties (Young, 1984;Yu and Matsui, 1994).…”
Section: Introductionmentioning
confidence: 99%